Peningkatan Pelayanan Berbasis Strategi Komunikasi Organisasi pada RSUD Luwu - Hele, Anindya Pertiwi; Maela, Nurannafi Farni Syam (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2018)
The purpose of this study is to describe the organization's communication strategy to improve patient service in Luwuk Regional Public Hospital. In this study, the researcher uses qualitative research method in order to know or to describe the facts of the events studied so that it facilitates the researcher to obtain objective data in order to know and to understand the Organization's Communication Strategy on Service in Luwuk Regional Public Hospital. The result of this research can be concluded that the organization communication strategy related to the effort of delivering message has not supported the occurrence of effective communication yet. This is because the message delivered verbally is unclear to the subordinate so that it needs to re-delivery and submission of information back, medicine naming verbally so that it is misidentified by by the nurse, via phone also raises the unclearness of messages and poor doctor's writing that sometimes complicate the task of a nurse so that it will give impact on service pattern. The second is timing; organizational communication strategy related to timing in the delivery of messages is still not optimal. Keywords: communication strategy, organization, service